OUR NATURE’S GREEN PROTECTORS - Akbarova Muxayyo Xusanovna; Gulamov Abdulaziz Khoshimjon oglu (Web of Journals Publishing, 2025)
This article provides information on the importance of green plants in nature in human life, especially their beneficial properties in maintaining health, including the Lycium (Goji) plant acclimatized in our country.
Keywords: Greening, Lycium, Goji, longevity fruit, antioxidant, sandy area.